Keberkesanan dan impak program latihan setara ijazah terhadap pegawai kanan Polis di kontijen Johor - Kamaruddin, Arsad (2012)
The study based on the design of this evaluation was to identify the effectiveness and impact from Program Training Program Equivalent First Degree for Senior Police Officer in the Royal Malaysian Police Force Contingent stationed in Johor. Overall population totaled 250 Senior Police Officer. From the number, only 125 people who have just randomly selected as respondents. Data for this study were collected using a set of questionnaires developed for this study. Out of a total of 152 questionnaires distributed, all in full has been returned and analyzed for this study using the software Statistical Package for Social Sciences (SPSS) involving descriptive statistics, Pearson correlation, and multiple linear regression analysis. The study found that participants were very satisfied with Training Program Equivalent First Degree as well as the study found the program very effective in the context of the acquisition of knowledge and skills upgrading. In terms of program impact, the study found that it gives a very high impact on behavior change and knowledge transfer. Therefore this study concludes that Program Latihan Setara Ijazah very important for the development of human capital senior police officer in Johor Contingent. This study suggests that such programs continue in the future with all of the focus on the improvement of each vulnerability